2017
DOI: 10.1051/matecconf/20179701002
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Salt Water on Chloride Penetration in Geopolymer Concrete

Abstract: Abstract. This paper presents the influence of chloride ion penetration in geopolymer concrete. Fly ash as based material for geopolymer concrete was used in this mixture. Fly ash was mixed with sodium hydroxide (NaOH) 8 M and sodium silicate (Na 2 SiO 3 ) as the alkali solution. The sizes of cylindrical specimens were prepared with a diameter of 100 mm and 200 mm high. Some specimens were immersed in salt water at a concentration of 3.5%, and other control specimens were cured in tap water for 30, 60, 90, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 13 publications
0
2
0
1
Order By: Relevance
“…Therefore, it has a positive effect on the durability of GPC. Halim and Ekaputri [101] examined the effect of salt water on the performance of GPC made of sodium silicate and 8 molar sodium hydroxides as the alkali solution and fly ash as binder material. They immersed some samples in 3.5% concentration of salt water, while other samples were cured in normal water, as a control samples.…”
Section: Chloride Ion Penetrationmentioning
confidence: 99%
“…Therefore, it has a positive effect on the durability of GPC. Halim and Ekaputri [101] examined the effect of salt water on the performance of GPC made of sodium silicate and 8 molar sodium hydroxides as the alkali solution and fly ash as binder material. They immersed some samples in 3.5% concentration of salt water, while other samples were cured in normal water, as a control samples.…”
Section: Chloride Ion Penetrationmentioning
confidence: 99%
“…Persyaratan untuk tebal selimut beton yang kontak langsung dengan udara atau tanah adalah 40-50 mm. [15] Penelitian ini juga bertujuan untuk menginvestigasi pengaruh variasi ketebalan lapisan mortar geopolimer terhadap kuat tekan beton normal yang direndam di lingkungan laut. Hasil penelitian ini diharapkan dapat memberikan wawasan baru dalam penggunaan mortar geopolimer sebagai material proteksi yang efisien dan tahan lama pada konstruksi struktur yang terpapar di lingkungan air laut.…”
Section: Pendahuluanunclassified
“…Past studies have confirmed that steam curing at a temperature range of 60 o C-80 o C contributes to faster strength development at early age [9] and promotes the reaction of geopolymerization [10,11]. On the other hand, some studies have suggested that moist curing is more recommended than wet curing [12]. Leaching of alkaline and some compound of alumina-silicates lead to the formation of more pores on the concrete surface.…”
Section: Introductionmentioning
confidence: 99%